Effet de l'amendement du substrat dalevage en differentes sources de calcium sur la croissance de Archachatina marginata. (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
Five hundred and sixty spat of Archachatina marginata (Swainson, 1821), of an average live weight of 2.89 ± 0.13 g with an average shell length of 2.34 ± 0.06 mm and aged around two weeks, were reared for 24 weeks in ten types of substrates. These substrates were composed of 2%, 5% and 10% of flour shell of snails, oysters and chicken eggs. A control substrate without amendment was also taken into account. In order to determine the best source and the best levels of calcium, all animals were fed with a mixture of leaves and fruits of papaya (Carica papaya). This study found that the quality of the substrate influences growth parameters of Archachatina marginata. The highest growth rates were achieved with flour of oyster shell and chicken eggs shell at rates of 10% amendment. These flours induce therefore good growth of Archachatina marginata and could be recommended as sources of amendment for the breeding practice of this species.